Nepal’s Legal Framework against Sexual Harassment: A Comprehensive Review - Sharma, Tribhuwon; Aryal, Bhagwan; Pokhrel, Mahesh; Shrestha, Roselini (International Research Journal of MMC, 2024)
Background: This in-depth analysis delves into Nepal's remarkable evolution in combatting and preventing sexual harassment through legal provisions. The review meticulously explores the policies articulated by the Nepal Law Commission, which have played a pivotal role in shaping the nation's approach to addressing and preventing sexual harassment. Objective: It aimed to explore key legislative acts, amendments, and special provisions that set Nepal apart in the fight against sexual harassment, emphasizing the country's commitment to fostering safe and respectful environments. Methods: The website of the Nepal Law Commission was the main information source, where 19 pertinent legislation pertaining to sexual harassment were carefully examined. Manual literature searches, desk reviews, and narrative reviews were used to synthesize the content. Both commonalities and distinct approaches were highlighted through a careful review and analysis of the specific sexual harassment-related laws of Nepal and comparison made in with neighboring South Asian countries. Results: In comparison to South Asian countries, Nepal has a strong legal system that reflects its unwavering commitment to ending sexual harassment. It has a wide variety of legislation that places an emphasis on accessibility and inclusion. Nepal's legal landscape is commended for its clarity, inclusivity, and proactive measures, while challenges such as potential overlaps among laws and the need for integrated coordination are recognized. Conclusions: The article emphasizes the continuous evolution and refinement of Nepal's legal framework, underscoring the importance of ongoing efforts, public awareness, and international collaboration in shaping effective and inclusive policies against sexual harassment.